Paddy residue for electricity generation in Malaysia: Emissions and cost saving - Mohd Shafie, Shafini; Othman, Zakirah; Hami, Norsiah (2018)
Paddy residue creates the huge potential in the power generation sector.In Malaysia, consumption of paddy residue for electricity generation can help to mitigate the GHG emission and the best solution for waste management activities.The forecast data on electricity generation is used to calculate the GHG emission and its saving when paddy residue is used for electricity generation.The government cost saving also identified when paddy residue substituted the coal fuel in electricity generation.Hopefully, the data obtained can motivate the stakeholder bodies in implementation paddy residue as electricity generation since their positive impact toward cost and emission saving.